Indigenous Peoples' participation in decision-making in the context of World Heritage Sites: how International Human Rights Law can help?. (2nd July 2016) - Barreiro Carril, Beatriz
Abstract: This article addresses the challenges of Indigenous Peoples' participation in conservation nomination processes and in the management of the sites they inhabit. It analyses the developments – conceptual and legal – produced both in UNESCO and in the United Nations Human Rights system for the inclusion of Indigenous People's interpretations and visions and the respect of their rights in the context of World Heritage Sites. The author argues that the inter-governmental composition of the World Heritage Committee can make the introduction of an Indigenous Peoples' rights-based approach in the World Heritage Convention decision-making processes extremely difficult; especially because some States have supported an outdated and manifestly wrong interpretation of sovereignty. This is why, in contrast to the traditional approach which focuses on 'specific' Indigenous Peoples norms, this paper suggests that a stronger emphasis on the recent developments in the International Human Rights system concerning the 'general' human right to take part in cultural life – which include Indigenous Peoples' rights – would be, strategically speaking, a better way to support the inclusion of a rights based-approach to the World Heritage Convention decision-making processes.